Antituberculosis Activity of Brotowali (Tinospora crispa) Extract and Fractions against Mycobacterium tuberculosis using Microplate Alamar Blue Assay Method - Retno Wahyuningrum; Ritmaleni Ritmaleni; Tatang Irianti; Subagus Wahyuono; Takushi Kaneko; Titik Nuryastuti (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Tuberculosis (TB), in which caused by pathogenic bacteria, Mycobacterium tuberculosis, has become the major causes of death among all of infectious diseases. The increasing incidence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) has created a need to discover a new antituberculosis drug candidate. The aim of this study was to screen extract and fractions of Tinospora crispa for activity against Mycobacterium tuberculosis H37Rv using the Microplate Alamar Blue Assay (MABA) method. T. crispa extract was prepared by maceration in ethanol (96%) and antituberculosis activity was carried out using MABA method. The result of this study showed that ethanolic extract of T. crispa exhibit antituberculosis activity with minimum inhibition concentration of 12.5 mg/ml.